Collaborative research in higher education: Benefits for scholars in tourism - Mkwizu, Kezia Herman (School of Tourism, Universitas Ciputra Surabaya, 2024)
Higher Education (HE) plays a key role in disseminating knowledge to the research community and society at large. In Africa, production of research output is a challenge. Past scholars have highlighted that collaboration in terms of co-authorship is needed to increase the research output. To expand literature on collaboration among scholars from different disciplines, this paper’s main objective was to explore collaborative research in HE focusing on the benefits for scholars. Specifically, this paper explores multidisciplinary collaborative research in HE with a focus on the benefits for scholars in tourism. The research methodology applied in this paper is a Scholarly Personal Narrative (SPN) method to avail experiences of collaborative research from the perspective of an African tourism scholar. Content analysis was used to provide relevant themes that address the objective of this paper. Findings reveal that multidisciplinary collaborative research in HE has benefits. Some of the benefits include “networking”, “sharing workload’, “integrating research skills” and “supporting team”. The outcome implies that HE institutions in Africa should encourage multidisciplinary collaborative research as a way of increasing knowledge production to benefit the academic community and non-academic community for the development of Africa.